PLAN ONION SEEDS IN A SEED ROW RESULTS OF EXPERIMENTAL STUDIES ON SLIDE FOUNDATION - Eshdavlatov, A (Innovative Development in Educational Activities, 2023)
The article presents the results of an experimental study to substantiate the radius of curvature of the front part of the opener runner and the applied vertical load on it of a seeder for sowing onion seeds in a belt-multi-row method.